Preliminary Survey of Mammals at Crocker Range Park (Park Headquarters), Sabah, Malaysia - Andrew Alek, Tuen; MA, Rahman; MA, Salleh (Researchgate, 2002)
Based on fieldwork in conjunction with the Crocker Range Expedition during October 1999 eight species of bats were recorded. Examination of Sabah Park mammals collection from Trus Madi, Kinabalu Park and Poring Hot Spring as well as search of the available literature revealed an additional 33 species of bats, giving an overall record of 41 species. These include 11 species of megachiropteran and 30 species of microchiropteran. Fifteen of the bats listed are known to roost in caves. None of the hats are endemic to Crocker Range Park but the naked bat, Cheiromeles torquatus, may be threatened.